INVENTARISASI JENIS-JENIS ZINGIBERACEAE DI HUTAN TELAGAH TAMAN NASIONAL GUNUNG LEUSER KABUPATEN LANGKAT SUMATERA UTARA - Melfa Aisyah Hutasuhut (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2018)
Zingiberaceae is one of perennial herbaceous plant that was unique to its rhizomes. This is because the Zingiberaceae contains evaporated oil or had an aromatic odor. This research was conducted in February to March 2018 in the Telagah Forest of Gunung Leuser National Park, Langkat Regency. This research used descriptive procedures with observation techniques. The result based on observations obtained 11 species of Zingiberaceae, with 7 Genus of Zingiberaceae. The Globba Genus has the most number of species, 4 species (Globba nawawii Ibrahim & K. Larsen; Globba paniculata Valeton; Globba patens Miq; and Globba pendula Roxb.), Etlingera Genus (Etlingera alatior (Jack) R.M. Sm.; and Etlingera littoralis (J. Konig) Giseke), Amomum Genus (Amomum ochreum Ridl.), Curcuma Genus (Curcuma sp.), Hedychium Genus (Hedychium coronarium Koenig.), Hornstedtia Genus (Hornstedtia tomentosa (Blume) bakh.f.) and Zingiber Genus (Zingiber multibracteata Holtt).Keywords: Zingiberaceae. Rhizomes, Gunung Leuser National Park.